Public Exposure to Natural Radioactivity Near Uranium Deposits in Manyoni Area, Central Tanzania - Shovi Sawe (Brazilian Journal of Radiation Sciences, 2023)
Assessment of public exposure to background radiation was performed in Manyoni, Tanzania to address public concerns following the discovery of uranium deposits in their neighborhoods. Results show that the highest concentrations of radionuclides are 112, 95 and 463 Bq.kg-1 for 226Ra, 232Th and 40K, respectively. The highest annual effective dose to the public is 2.91 mSv.y-1 with a mean value of 1.29 mSv.y-1. Authorities may use these results to address public concerns as well as the baseline information. Further investigations on public exposures in Manyoni are recommended.